Tindak pidana pencucian uang - Utomo, Joko Margo; Sari, Tri Yunita (Indonesian Journal of Law and Justice, 2024)
The phenomenon of money laundering is increasingly troubling the public, especially related to the practice of trading fraud and trading robots that deceive many victims. Money laundering is a serious economic crime that uses financial institutions to hide the origin of illegal funds. The research uses literature research methods to collect and analyze information from various reliable sources. The results show that money laundering practices involve a variety of complex methods such as real estate, foreign transactions, and false income generation. The Financial Transaction Reporting and Analysis Center (PPATK) plays an important role in the prevention and enforcement of this crime in Indonesia, with independent authority to tackle money laundering and terrorism financing. This research provides in-depth insight into the concept, operational mechanism, and efforts to prevent money laundering crimes.